Ingredients for Thriving Urban Communities in a Post-COVID World - Horn, Jennifer Licad (Archīum Ateneo, 2021)
Like the inaugural book; Makisawsaw Recipes x Ideas 2: Community Gardens Edition continues the conversation surrounding the food we eat; in the context of solidarity with the urban poor and small farmers. Recognizing the power of food to bridge differences; and inspired by the dream of making ecological and biodiverse food gardens as common as sari-sari stores; the book features 70+ healthy; delicious; plant-based recipes that invite you to eat & act in solidarity—from the garden to the kitchen. The first edition of Makisawsaw: Recipes x Ideas (edited by Mabi David and Karla Rey; was listed on CNN Philippines’ “The best Filipino books of the 2010s”). Critically and commercially lauded; it wanted to offer another way of looking at our food—one that goes beyond personal preference and is shaped by economic; social; and political pressures that affect everyone. Put together after the violent dispersal of NutriAsia workers fighting for their labor rights; part of the sales of the book helped to raise bail funds in solidarity with the NutriAsia workers. This time; we take the discussion to community food gardens and golden rice; with recipes and ideas from Gertrudes Olaer of the Food Today; Food Tomorrow Payatas gardens; Jordy Navarra of Toyo Eatery; Chele Gonzales and Carlos Villaflor of Gallery by Chele; Margarita Forés; Asha Peri of Ecology of Food; Rap Cristobal of Purple Yam; Allan Briones of Peninsula Manila; Tey Lopez of The Vegan Neighbors Philippines; Astig Vegan; Me and My Veg Mouth; and many more! All proceeds of the sales will go into supporting the Food Today; Food Tomorrow initiative; under the coalition Slow Food Sari-sari; in partnership with Pinagkaisang Lakas ng Mamamayan (PLM/People’s United Strength).